Mathematical methods for finance : tools for asset and risk management - Focardi, Sergio M.; Fabozzi, Frank J.; Bali, Turan G. (Hoboken, New Jersey : Wiley, 2013)
The mathematical and statistical tools needed in the rapidly growing quantitative finance field With the rapid growth in quantitative finance, practitioners must achieve a high level of proficiency in math and statistics. Mathematical Methods and Statistical Tools for Finance, part of the Frank J. Fabozzi Series, has been created with this in mind. Designed to provide the tools needed to apply finance theory to real world financial markets, this book offers a wealth of insights and guidance in practical applications. It contains applications that are broader in scope from what is covered in a.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Finance -- Mathematical methods; Asset-liability management -- Mathematical models; Risk management -- Mathematical models; Finance -- Mathematical models; Asset-liability management -- Mathematical models; Risk management -- Mathematical models; BUSINESS & ECONOMICS -- Finance; Asset-liability management -- Mathematical models; Finance -- Mathematical models; Risk management -- Mathematical models; Finance / Mathematical models; Asset-liability management / Mathematical models; Risk management / Mathematical models; Electronic books